TINJAUAN YURIDIS PENGA WASAN KPP PRATAMA TERHADAP SURAT SETORAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN SEHUBUNGAN DENGAN PROSES PERALIHAN HAK ATAS TANAH - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The research was conducted to study implementation of monitoring by KPP Pratama over Payment Slip of Acquisition Duty on Right of Land and Buildingin relation to transferprocess of right of land and building and to identify Obstacles the KPP Pratama have in monitoring Payment Slip of Acquisition Duty on Rightof Land and Building. It was juridical empiricalresearchwith qualitativemethod by describing situationand condition that relate to existing regulations on this research topic. It emphasizedon primarydata obtained from interviewin KPP Pratama and Sleman BPN, supported with secondary data from documentary study of primary, Secondary and tertiary law material. Data obtained from the research after qualitative analysis indicated that Implementation of monitoringby KPP Pratama over PaymentSlip of Acquisition Dutyon Rightof Land and Buildingin relationto transfer process of right of land and building was started with file handling by Service Section! Determining section. Then SSB examination was done by assigned examining personnel, whichits regulation was givento head of KPP Pratama by coordinatingwith head of Service Section. This examinationwas done using research working paper form. When SSB field examinationis.necessary head of KPPBB/KPP Pratama issued SSB Field ExaminationTask Letter. For examined SSB, it was stamped with stamp shape regulatedin Appendix3 of Tax Directorate General regulation number PER-16.PJI2008 on examination procedure for Payment Slip of Acquisition Duty on Right of Land and Building. In contrary if it was not Appropriate (for example,less paid), it would be returned and asked to fulfill the payment to saving state fund. Obstacles that KPP Pratama face were limited human resource in 8SB examination,in compatibility between map in PBB and draw in certificate,no graphical map (no data in KPP Pratama database), and differencein data with in certificate and realityin field of sale-buyobject